Oxygen titration after resuscitation from out-of-hospital cardiac arrest: A multi-centre, randomised controlled pilot study (the EXACT pilot trial) - Bray, Janet; Hein, C.; Smith, K.; Stephenson, M.; Grantham, H.; Finn, Judith; Stub, D.; Cameron, P.; Bernard, S. (Elsevier, 2018)
© 2018 Elsevier B.V. Introduction: Recent studies suggest the administration of 100% oxygen to hyperoxic levels following return-of-spontaneous-circulation (ROSC) post-cardiac arrest may be harmful. However, the feasibility and safety of oxygen titration in the prehospital setting is unknown. We conducted a multi-centre, phase-2 study testing whether prehospital titration of oxygen results in an equivalent number of patients arriving at hospital with oxygen saturations SpO2 = 94%. Methods: We enrolled unconscious adults with: sustained ROSC; initial shockable rhythm; an advanced airway; and an SpO2 = 95%. Initially (Sept 2015–March 2016) patients were randomised 1:1 to either 2 L/minute (L/min) oxygen (titrated) or >10 L/min oxygen (control) via a bag-valve reservoir. However, one site experienced a high number of desaturations (SpO2 < 94%) in the titrated arm and this arm was changed (April 2016) to an initial reduction of oxygen to 4 L/min then, if tolerated, to 2 L/min, and the desaturation limit was decreased to <90%. Results: We randomised 61 patients to titrated (n = 37: 2L/min = 20 and 2–4 L/min = 17) oxygen or control (n = 24). Patients allocated to titrated oxygen were more likely to desaturate compared to controls ((SpO2 < 94%: 43% vs. 4%, p = 0.001; SpO2 < 90%: 19% vs. 4%, p = 0.09). The majority of desaturations (81%) occurred at 2L/min. On arrival at hospital the majority of patients had a SpO2 = 94% (titrated: 90% vs. control: 100%) and all patients had a SpO2 = 90%. One patient (control) re-arrested. Survival to hospital discharge was similar. Conclusion: Oxygen titration post-ROSC is feasible in the prehospital environment, but incremental titration commencing at 4L/min oxygen flow may be needed to maintain an oxygen saturation >90% (NCT02499042).